Fiscal Decentralization and Government Corruption: Evidence from U.S. States. (3rd March 2020) - Shon, Jongmin; Cho, Yoon Kyoung
Abstract : The demand for decentralized government has increased with widespread political devolution, because it is perceived as a more efficient and accountable form of government. However, the limited autonomy in subnational governments is criticized, for fiscal decentralization has the potential to increase corruption and to harm government accountability, because representatives and bureaucrats in local governments may be involved in private corporations and other special interest groups. Moreover, little attention has been paid to U.S. state and local governments. This study considers multiple perspectives in fiscal decentralization in the state governments, and examines the effects of fiscal decentralization on state corruption. The empirical findings contribute to the argument in the extant research that corruption in U.S. state governments increases in a more decentralized structure.